Family relationship of depressed and not depressed Filipino adolescents - Dizon, Chorina Eloisa T. (Animo Repository, 1999)
The study was conducted to determine difference of family relationships of the depressed and not depressed. The 60 participants (30 depressed and 30 not depressed) were given the Carroll Rating Scale for Depression, a psychological test to assess whether the adolescent was depressed or not depressed. They were then interviewed regarding their relationships with their parents and their siblings. It was found out that most of the depressed and not depressed respondents were closer to their mother than their father. The not depressed were more open to parents and are contented with the relationship they have with their parents. Regarding the respondent's relationship to siblings, the depressed were closer to their siblings.